Safety and efficacy of molnupiravir in SARS‐CoV‐2‐infected patients: A real‐life experience. Issue 11 (2nd August 2022) - De Vito, Andrea; Colpani, Agnese; Bitti, Alessandra; Zauli, Beatrice; Meloni, Maria Chiara; Fois, Marco; Denti, Lucia; Bacciu, Sara; Marcia, Claudia; Maida, Ivana; Babudieri, Sergio; Madeddu, Giordano
Abstract: Since the start of the severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) pandemic, several treatments have been proposed to cure coronavirus disease 2019 (COVID‐19) and prevent it. Molnupiravir is a ribonucleoside prodrug of N ‐hydroxycytidine with an in vitro and in vivo activity against SARS‐CoV‐2. We conducted a retrospective cohort study that included all people treated with molnupiravir between January 10, 2022, and March 31, 2022, at the University Hospital of Sassari. Molnupiravir was prescribed, according to the Italian Agency of Drug indications, to patients with recent symptom onset (≤5 days), no need for oxygen supplementation, and with a high risk of disease progression for the presence of chronic diseases. We included 192 people with a mean age of 70.4 ± 15.4 years, with 144 (75%) patients over 60 years. During the follow‐up, 20 (10.4%) patients showed a disease progression. At the multivariate analysis, older age, having neurological disease, having dyspnea at the onset of the symptoms, and acquiring SARS‐CoV‐2 infection during hospital admission were associated with an increased risk of progression. In contrast, an early start of treatment was associated with a reduced risk of disease progression. Molnupiravir was also extremely safe since 13 (6.8%) adverse events were reported, with only one interruption. Our study shows that monlupiravir confirmed its efficacy and safety in a real‐life cohort that included a high percentage of elderly people with a high comorbidity burden.